PENGETAHUAN MASYARAKAT MENGENAI PENANGANAN REHABILITASI MEDIK PADA PENDERITA STROKE DI KELURAHAN PINAESAAN KECAMATAN WENANG KOTA MANADO - Sundah, Antony B. M.; Angliadi, Engeline; Sengkey, Lidwina (Universitas Sam Ratulangi, 2014)
Abstract: Medical rehabilitation in patients with stroke is an action to improve motor function, speech, cognitive, and other function are impaired, as well as social and mental readaptation to restore interpersonal relationship and social activity, and train the patient in order to carry out activities of daily living. Stroke is a disease that is caused by blockages in the blood vessels of the brain or the rupture of blood vessels in the brain which leads to reduces oxygen supply to certain parts of the brain therefore the brain tissue is damaged or died. Stroke is more common made disability than dead. Permanent disability occurs because the patient is not get rehabilitation and frequently family indulged excessive helped patients with excessive and makes the patient lying passively waiting for conditions become better. Because that, medical rehabilitation in patient with stroke is very important to be able to restore the condition of stroke patients in order to indulge as normal person. The purpose of this study was to obtain data on the public knowledge of patient with stroke in the rehabilitation of sub-district Wenang district Pinaesaan. This study is a descriptive study with a quantitative approach using cross-sectional methods. Subjects were adult people living in sub-district Wenang district Pinaesaan. From the 89 respondent who are willing to study respondents, by sex obtained 34 respondents (38.2%) men, and 55 respondents (61.8%) women. Based on the level of knowledge, elemantary school education gained 2 respondents (2.2%), high school education 68 respondents (76.4%), and university education 19 respondents (21.3%). Based on public knowledge of medical rehabilitation in stroke patients, good knowledge obtained 34 respondents (38.2%), moderate knowledge obtained 48 respondents (53.9%), and lack of knowledge obtained 7 respondents (7.9%). Conclusion: Based on this study, the level of education affect the knowledge of medical rehabilitation in stroke patients. Keywords: knowledge, Medical Rehabilitation, Stroke. Abstrak: Rehabilitasi medik pada penderita stroke merupakan tindakan untuk memperbaiki fungsi motorik, wicara, kognitif dan fungsi lain yang terganggu, serta readaptasi sosial dan mental untuk memulihkan hubungan interpersonal dan aktivitas sosisal, dan melatih penderita agar dapat melaksanakan aktivitas kehidupan sehari-hari. Stroke merupakan penyakit yang terjadi akibat penyumbatan pada pembuluh darah otak atau pecahnya pembuluh darah di otak sehingga jaringan otak tersebut rusak atau mati. Stroke lebih sering meninggalkan kecacatan dibandingkan kematian. Kecacatan menetap terjadi karena penderita tidak diberi rehabilitasi dengan baik dan keluarga seringkali memanjakan penderita dengan membantu secara berlebihan dan menjadikan penderita terbaring pasif menunggu kondisi menjadi lebih baik. Karena itu, rehabilitasi medik pada penderita stroke sangat penting untuk dapat mengembalikan kondisi penderita stroke agar dapat beraktivitas seperti orang normal. Tujuan penelitian ini adalah untuk memperoleh data pengetahuan masyarakat tentang rehabilitasi pada penderita stroke di kelurahan Pinaesaan Kecamatan Wenang. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif dengan metode cross-sectional. Subjek penelitian adalah masyarakat dewasa yang bermukim di kelurahan Pinaesaan kecamatan Wenang. Dari 89 responden yang bersedia menjadi responden penelitian, berdasarkan jenis kelamin didapatkan 34 responden (38,2%) pria, dan 55 responden (61,8%) wanita. Berdasarkan tingkat pengetahuan, didapatkan pendidikan dasar 2 responden (2,2%), pendidikan menengah 68 responden (76,4%), dan pendidikan tinggi 19 responden (21,3%). Berdasarkan pengetahuan masyarakat tentang rehabilitasi medik pada penderita stroke, didapatkan pengetahuan baik 34 responden (38,2%), pengetahuan sedang 48 responden (53,9%), dan pengetahuan kurang 7 responden (7,9%). Simpulan: Berdasarkan penelitian ini tingkat pendidikan akan mempengaruhi pengetahuan rehabilitasi medik pada penderita stroke. Kata kunci: Pengetahuan, Rehabilitasi Medik, Stroke.